Black Discrimination in Sembene Ousmane's short story: Gadis Berkulit Hitam, as A Deconstruction Study - Dwi Nur Cahyani (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
This study discusses the discrimination that occurs in the short story of the Gadis Berkulit Hitam. The discrimination is due to the oppression of white people against black people. The concept of black and white is an inverse which cannot be separated from one another. The inverse gives a binary opposition and can form a new meaning for a person. Black and white is part of the identity of post-colonialism. In the short story Gadis Berkulit Hitam, the main character is a country girl who goes to France to achieve her dream of coveted luxury and success. But it never came true because she was just a black girl. Through a deconstruction approach, the writer begins to try to come up with a new identity for the main character in the short story by taking advantage of the language gap. This uncertainty eventually led to the absence of the main character. Therefore, a person's identity can change and the process of change is called difference which means to distinguish and be different. The writer tries to apply this concept to bring up a new identity for black girls by deconstructing the pre-formed hierarchy. In conclusion, the black and white construction inherent in society is a rigid construction and cannot be justified anymore. The boundaries that become the identity and separate the binary opposition cannot be strictly maintained.